The first complete scientific grammar of Skolt Saami in English - Koponen, Eino; Rueter, Jack (Finnisch-Ugrische Forschungen, 2016)
Timothy Feist: A Grammar of Skolt Saami. Mémoires de la Société Finno-Ougrienne 273. Finno-Ugrian Society. Helsinki 2015. 414 p.